ANALISA PENGARUH KEBIJAKAN MONETER DAN KEBIJAKAN FISKAL TERHADAP PERTUMBUHAN KEPARIWISATAAN DI DAERAH ISTIMEWA YOGYAKARTA - Pratama Nugraha, Budi Sutiono (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The economic growth of a country so far has a goal to achieve the welfare of society in a sustainable manner. Community economic activities become a benchmark, to determine the level of welfare of a country or region. Economic development and growth cannot be separated so that it still needs to maintain the economic role in this region. In accordance with economic growth to remain on a positive trend, the necessary interactions between monetary and fiscal policies. However, both policies have different authorities. If monetary policy is more controlled by the central government, fiscal policy with fiscal decentralization has two elements from the center and the regions. The interaction between monetary and fiscal policies is believed to have a good influence on the growth in various areas of the economy of the region.Therefore in this study it was found that the stability of Monetary Policy and Fiscal Policy had a positive influence on the growth of the Tourism sector, especially in the Special Region of Yogyakarta which was the object of research. So that the impact of the growth of the tourism sector can reduce unemployment and increase public opinion in the area.